Is laparoscopic surgery the answer to generalised purulent peritonitis from complicated appendicitis? - Ndofor, Brown Chwifeh (My University, 2012)
Aim To compare the different outcomes in a single institution between patients with generalised purulent peritonitis from complicated appendicitis diagnosed intraoperatively which were managed laparoscopically to those managed via the open approach. Methods Data was collected from all cases admitted at Sebokeng Hospital over the past two years (2008 & 2009) with an intraoperative diagnosis of generalised purulent peritonitis from complicated appendicitis. Cases which were managed laparoscopically or by the open approach were analysed. The parameters analysed were the demographic findings, the theater duration, complications, and days to the commencement of full ward diet, and length of hospital stay. Results During the study period, a total of 120 cases of appendicectomies with generalised purulent peritonitis were performed. Of these, 58 cases underwent open appendicectomy (OA) and 62 cases had laparoscopic appendicectomy (LA). Both groups were comparable in the demographics and preoperative findings. The theater duration was significantly higher in the LA group (115.8 minutes for LA compared to 86.7 minutes for OA. The rate of intraabdominal sepsis was also higher in the LA group (12.9% for LA and 8.6% for OA). Both groups showed no statistical significant difference between the wound sepsis or port site sepsis rate, the days to commencement of full ward diet and length of hospital stay. More time was spent in ICU/HCU in the OA group an average of 3.7 days as opposed to 2 days in the LA group. However age, the duration of symptoms, the clinical presentation and the white blood cell count (WBC) were influencing factors to the outcome of the OA group. Conclusion Generalised purulent peritonitis from complicated appendicitis can be managed successfully laparoscopically. Both approaches are feasible, safe and have comparable outcomes. Where facilities are adequately skilled and resourced, the laparoscopic approach should be considered the procedure of choice for complicated purulent appendicitis because it is less influenced by preoperative findings and shows a trend towards less postoperative complications.
Keywords: Appendicitis